Socioeconomic status, secondary prevention activities during the first year after a myocardial infarction and target attainments. (25th November 2020) - Ohm, J; Skoglund, P.H; Habel, H; Sundstrom, J; Hambraeus, K; Jernberg, T; Svensson, P
Abstract: Background: Socioeconomic status (SES) is a strong predictor of recurrent events post-myocardial infarction (MI) with unclear underlying mechanisms. To what extent SES is associated with secondary prevention activities (SPAs) and attainment of quality-of-care treatment goals is unknown. Purpose: We aimed to assess the association between SES and SPAs during the first year post-MI and attained treatment targets at the 1-year follow-up. Methods: Nationwide Swedeheart registry-based cohort study on 30, 191 18–76 year old 11–15 month survivors of a first MI (8, 180 women) 2006–2013. Complementary individual-level clinical data and data on SES (age and gender stratified quintiles of disposable income, level of education, and marital status), were linked from other national registries. Associations between SES and the outcomes were estimated in multivariable logistic regression models with basic adjustment for potential registry-related confounding. Results: The associations between all indicators of SES and attendance to patient education and physical training programs were strong, moderate for dietary program attendance but absent for participation in smoking cessation program (Table 1). Higher SES was also associated with repeated lipid profile measurements and the highest vs lowest income with intensified statin therapy. Correspondingly, higher SES was associated with having achieved target levels of LDL-C, blood pressure, and HbA1c as well as with persistence to and being on high intensity statin treatment (Figure 1). Further, higher SES was strongly associated with having quit smoking. No association with income was however observed regarding the weekly physical activity goal. Conclusions: Higher SES was strongly associated with most SPAs including programs aiming at life style change and risk factor control as well as with attainment of corresponding secondary prevention targets. This may be explanatory for higher long-term risk of recurrent disease. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Stockholm City Council and The Swedish Heart and Lung Association